Legitimizing the Artist : Manifesto Writing and European Modernism 1885-1915 - Somigli, Luca (Book collections on Project MUSE., 2015)
In this work Luca Somigli discusses several European artistic movements - decadentism, Italian futurism, vorticism, and imagism - and argues for the centrality of the works of F.T. Marinetti in the transition from a fin de siecle decadent poetics, exemplified by the manifestoes of Anatole Baju, to a properly avant-garde project.